2000
DOI: 10.1161/01.cir.101.7.777
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Geometry and Function Preceding Neurally Mediated Syncope

Abstract: Background-Neurally mediated syncope has been associated with increased left ventricular (LV) fractional shortening (FS) during tilt testing, which is consistent with the hypothesis that the stimulation of LV mechanoreceptors leads to reflex hypotension and/or bradycardia. However, FS does not represent true LV contractility because of its dependence on afterload and preload. Methods and Results-To elucidate the role of increased contractility in the mediation of neurally mediated syncope, we compared echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 33 publications
3
44
1
Order By: Relevance
“…15 During the first and intermediate phases of TT, the reduction or the rate of reduction in SV or end-diastolic volume has been seen to be greater in patients with positive TT than in controls. 11,12,14,17,18 In the studies by de Jong-de Vos van Steenwijk et al 21 and Novak et al, 23 a decrease in SV and CO was not observed in patients with positive TT before loss of consciousness, and hypotension appeared secondary to a fall in calculated TPR. However, the former study investigated paediatric subjects without a history of spontaneous syncope, who might show a different haemodynamic behaviour.…”
Section: Previous Studiesmentioning
confidence: 94%
“…15 During the first and intermediate phases of TT, the reduction or the rate of reduction in SV or end-diastolic volume has been seen to be greater in patients with positive TT than in controls. 11,12,14,17,18 In the studies by de Jong-de Vos van Steenwijk et al 21 and Novak et al, 23 a decrease in SV and CO was not observed in patients with positive TT before loss of consciousness, and hypotension appeared secondary to a fall in calculated TPR. However, the former study investigated paediatric subjects without a history of spontaneous syncope, who might show a different haemodynamic behaviour.…”
Section: Previous Studiesmentioning
confidence: 94%
“…In contrast, other studies have not found a significant increase of adrenaline in VVS [13,15,25]. Myocardial hypercontractility, which could be expected as a possible result of an adrenaline surge preceding VVS, was not documented by echocardiography [26]. By measuring peak ventricular acceleration, Brignole et al showed that VVS may occur at both low and high levels of ventricular contractility [27].…”
Section: Discussionmentioning
confidence: 97%
“…Also, it has been assumed that vigorous LV contractions due to increased sympathetic tone stimulate afferent C receptors which in turn activate vagal tone [19], and some investigators have reported LV hypercontractility before syncope during the HUTT [7,8,9]. However, other previous studies have failed to verify the increased LV contractility as the initiating factor of hemodynamic changes in HUTT-induced VVS [5,10]. The current study was designed to give an account of those conflicting results and we postulated that a disregulated activation of the autonomic nervous system might promptly begin at the time of venous pooling.…”
Section: Discussionmentioning
confidence: 99%
“…However, that pathophysiologic concept and therapies in patients with VVS are largely based on assumptions or logical deductions made without sufficient data [2]. The Bezold-Jarisch reflex is believed to be triggered by venous pooling, a compensatory activation of the sympathetic nervous system, and/or reflex hypercontractility of the LV which is relatively underfilled [3,4,5,6]. In fact, there have been some reports observing the vigorous LV contractions before syncope [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation